Improving employee performance through coaching A competency-based Approach to skillful coaching to encourage productivity - Donahue, Wesley E. (Pennsylvania Centrestar Learning, 2022)
Supervisors are often told that performance feedback is necessary to improve how employees work, and supervisors are encouraged to give feedback both formally and informally. Yet reports indicate that 43 percent of employees receive the same negative feedback on their performance evaluations year after year, and only a third make improvements. Why is this?
Includes Index
Keywords: Employees--Training of. | Employee motivation. | Mentoring in business. | Labor productivity. | Performance standards